Effect of sample delivery conditions on Renin-Angiotensin-Aldosterone System (RAAS) assay. (1st July 2020) - Fu, Yu; Ge, Shibin; Qiu, Xueting; Cui, Rongrong; Zhang, Chen; Xu, Xindan; Li, Jianhua; Feng, Jianlin; Bai, Jianling; Sun, Min; Liu, Wei
Abstract: Renin-Angiotensin-Aldosterone System (RAAS) measurements are influenced by several factors. We investigated the effect of sample delivery conditions on RAAS measurements including sample storage temperature and time. Blood samples were collected from thirty participants using enzyme inhibitor tubes and serum separation gel evacuated tubes. Plasma and serum from fresh blood samples without further storage (as baseline), and from blood samples that were stored at either 0 °C, 4 °C, or 25 °C for 3 h, 6 h and 24 h, respectively, were extracted and stored at −30 °C for batch measurements using radioimmunoassay. Concentrations of Aldosterone (Ald) decreased following delivery temperature and time, and were significantly different when samples were set aside at 0 °C for 24 h ( p  < .01), 4 °C for 6 h ( p  < .01), and 25 °C for 3 h ( p  < .05). However, levels of Angiotensin (Ang I) increased following delivery temperature and time, and were significantly different when samples were set aside at 0 °C and 4 °C for 6 h ( p  < .05) and at 25 °C for 3 h ( p  < .001). However, no changes were observed for the concentrations of plasma renin activity (PRA) and Ang II, except for Ang II which increased significantly when samples were set aside at 25 °C for 24 h ( p  < .001). Our results indicate that samples used for RAAS measurement should be placed at a low temperature and analyzed as soon as possible after collection.